Modulation of interleukin 1 beta gene expression using antisense phosphorothioate oligonucleotides. - Manson, J; Brown, T; Duff, G (1990)
The production of interleukin 1 beta (IL1 beta) in lipopolysaccharide (LPS) stimulated monocytes was inhibited by 98% using antisense phosphorothioate oligonucleotides complementary to the 5' untranslated and exon 6 regions of IL1 beta mRNA. A sense phosphorothioate oligonucleotide failed to inhibit IL1 beta production. The inhibition of IL1 beta synthesis was not due to reduced cell viability and [35S]methionine incorporation showed that it could not be accounted for by an overall inhibition in protein synthesis. Tumour necrosis factor (TNF) and IL1 alpha production was also inhibited but to a lesser extent than IL1 beta. The use of antisense phosphorothioate oligonucleotides to inhibit IL1 production should enable the complex pathways of IL1 regulation to be elucidated and provide information on the biological role of these cytokines.